Spatial variability of Mycosphaerella coffeicola (Cooke) populations in coffee plantations, State of Mexico - Figueroa-Figueroa, Dulce Karen; Lara-Vázquez, Fidel; Ramírez-Dávila, José Francisco; Pérez-Constantino, Aurelio; Acosta-Guadarrama, Agustín David; Galacho-Jiménez, Federico Benjamín (Revista Mexicana de Ciencias Agrícolas, 2025)
Coffee is an important crop in Mexico and the State of Mexico is a producing state affected by the iron spot disease caused by the fungus Mycosphaerella coffeicola; this disease reduces the synthetic area, causes defoliation and can affect the quality of beans. Its control is limited due to the lack of knowledge of its spatial distribution within the plots. This study determined the distribution of iron spot in coffee using geostatistical techniques. Semivariograms and distribution maps were made by ordinary kriging, estimating the infested area. The incidence varied and correlated with temperature and relative humidity. An aggregate distribution that fitted theoretical models (Gaussian and spherical) was observed. Infestation was not uniform in the plots, suggesting that targeted control can optimize costs and improve the sustainability of crop management.